On change management for enterprise accounting system: iterative content analysis for success factors - Hamzah Ritchi; Ade Laide Debora (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2020)
The benefits, challenges, and factors that influence the success and failure in implementing ERP have been extensively studied by the previous researchers. In general, the existing literature focuses on general perspectives in organizational contexts. Not many studies have identified the success factors of change management within ERP implementation. Furthermore, few studies attempted to empirically verify these factors. In addition to information system success theory and change management, this study also employed content analysis on SAP Financial and Controlling module. This study attempted to understand the success factors through data reduction mapping, data display, and verification by employing Miles and Huberman data analysis model. Through three iterations based on 26 selected literatures, the top ten initial indicators and three axially coded indicators were derived to be verified as key success factors for change management in implementing Financial and Controlling SAP. The results of this study are to provide an important input for ERP change management initiatives.